2012
DOI: 10.1364/ao.51.003847
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature atmospheric pressure argon plasma treatment and hybrid laser-plasma ablation of barite crown and heavy flint glass

Abstract: We report on atmospheric pressure argon plasma-based surface treatment and hybrid laser-plasma ablation of barite crown glass N-BaK4 and heavy flint glass SF5. By pure plasma treatment, a significant surface smoothing, as well as an increase in both the surface energy and the strength of the investigated glass surfaces, was achieved. It was shown that for both glasses, hybrid laser plasma ablation allows an increase in the ablation depth by a factor of 2.1 with respect to pure laser ablation. The ablated volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Such surface smoothing of optical glasses was already observed in previous work where the same plasma source and treatment procedure was applied to barite crown glass NBaK4 and heavy flint glass SF5. After a plasma treatment duration of 60 seconds, Ra was reduced by 7.8% (N-BaK4) and 59.7% (SF5), respectively [12]. Generally, a reduction in surface roughness comes along with a decrease of the surface contact angle, corresponding to an increase in total surface energy γ s [13].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Such surface smoothing of optical glasses was already observed in previous work where the same plasma source and treatment procedure was applied to barite crown glass NBaK4 and heavy flint glass SF5. After a plasma treatment duration of 60 seconds, Ra was reduced by 7.8% (N-BaK4) and 59.7% (SF5), respectively [12]. Generally, a reduction in surface roughness comes along with a decrease of the surface contact angle, corresponding to an increase in total surface energy γ s [13].…”
Section: Resultsmentioning
confidence: 98%
“…Second, material removal can be due to the deexcitation of excited argon and metastable argon species and an accompanying energy transfer to the sample surface. Here, the possible underlying effects are electron quenching, twoand three-body collisions with argon atoms and Penning ionisation at the sample surface [12]. The existence of such species in the near-surface area can most likely be assumed due the direct plasma ignition on the substrate based on electron excitation and ion-impact excitation in the plasma sheath close to the sample surface [18] and/or resonant neutralisation.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of such simultaneous plasma-assisted ablation was already shown in previous work where argon was used as process gas [32][33][34]. One has to consider that in this case, the advantage was taken of plasma-physical mechanisms instead of plasma-chemical effects.…”
Section: Discussionmentioning
confidence: 97%
“…By collisions and the related de-excitation of such argon species, an additional energy deposition in the near-surface region of the substrate is achieved [7,8]. For such a simultaneous process, the focused laser beam is guided coaxially to an APP-beam or APP-jet, respectively.…”
Section: Simultaneous Laser-plasma Ablationmentioning
confidence: 99%
“…It was further shown that a pure argon APP-treatment without applying any laser irradiation allows a surface smoothing of the investigated glasses. After a plasma treatment of 60 seconds in duration, the root mean squared roughness rq was reduced by 18.8 % (N-BaK4) and 64.9 % (SF5), respectively [7]. …”
mentioning
confidence: 97%